2021
DOI: 10.31219/osf.io/mcdsq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interventions that Influence Animal-Product Consumption: A Meta-Review

Abstract: Transitioning toward more plant-based diets can alleviate health and sustainability challenges. However, research on interventions that influence animal-product consumption remains fragmented and inaccessible to researchers and practitioners. We conducted an overview of systematic reviews, also known as a meta-review. We searched five databases for reviews that examined interventions that influence (increase or decrease) the consumption of animal products. We quantitatively summarised results using individual … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Previous studies demonstrate that it is possible to experimentally affect meat consumption, at least in the short term (Cordts et al, 2014;Kunst and Hohle, 2016;Carfora et al, 2017Carfora et al, , 2019Amiot et al, 2018;Dowsett et al, 2018; for meta-analyzes see Grundy et al, 2021;Kwasny et al, 2022). It appears from a review of the interventions that shortterm outcomes, such as the immediate choice of foods, could be more amenable to change than more general habits and attitudes (Dowsett et al, 2018).…”
Section: Meat-reduction Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrate that it is possible to experimentally affect meat consumption, at least in the short term (Cordts et al, 2014;Kunst and Hohle, 2016;Carfora et al, 2017Carfora et al, , 2019Amiot et al, 2018;Dowsett et al, 2018; for meta-analyzes see Grundy et al, 2021;Kwasny et al, 2022). It appears from a review of the interventions that shortterm outcomes, such as the immediate choice of foods, could be more amenable to change than more general habits and attitudes (Dowsett et al, 2018).…”
Section: Meat-reduction Interventionsmentioning
confidence: 99%
“…Also, matching messages with the needs of consumers (e.g., their values or decision stages) increases their effectiveness (Kwasny et al, 2022). Finally, contextual factors, such as nudging or enhancing the visibility/ availability of vegetarian options, have proven helpful in encouraging meat-free options (Grundy et al, 2021;Kwasny et al, 2022).…”
Section: Meat-reduction Interventionsmentioning
confidence: 99%
“…There are theoretical reasons to expect that individuals will seek to conform to perceived social norms (e.g., Cialdini & Trost 1998), including in their attitudes and behaviors towards farmed animals (Delon, 2018). Some studies provide evidence that emphasizing information about people's attitudes and behaviors towards animals and how this is changing over time can affect the audience's own attitudes and behavior (e.g., Sparkman & Walton, 2017;Grundy et al, 2021).…”
Section: Perceived Social Attitudesmentioning
confidence: 99%
“…Caldwell's (2016) experiment found that participants who read articles about animal welfare changes "were more likely to intend to reduce their consumption of animal products than participants who read the control articles." More broadly, Mathur et al's (2021) meta-analysis found that providing information about farmed animals or their welfare appeared to consistently reduce reported meat consumption or consumption intentions. However, it is unclear whether animal welfare reforms also affect willingness to support further institutional changes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reviews have explored various measures and policies to promote dietary changes and reduce food waste, but these reviews have limitations in their scope and focus. Some concentrate exclusively on reducing consumption of animal-source foods [24,30], while others examine interventions that aim to induce behaviour changes, without considering environmental impact [21,22,25,31]. Some reviews focus solely on specific types of policies or outcomes, such as digital behavioural interventions [31], climate change mitigation [32,33], food waste reduction [32] or health [20,24,34].…”
Section: Introductionmentioning
confidence: 99%